If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-3p + 2) = 35 Reorder the terms: 7(2 + -3p) = 35 (2 * 7 + -3p * 7) = 35 (14 + -21p) = 35 Solving 14 + -21p = 35 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -21p = 35 + -14 Combine like terms: 14 + -14 = 0 0 + -21p = 35 + -14 -21p = 35 + -14 Combine like terms: 35 + -14 = 21 -21p = 21 Divide each side by '-21'. p = -1 Simplifying p = -1
| 6+2x=22 | | 4lnx=12 | | -3x+17=-4x+16 | | 6+5j=33 | | p^5=1-2p^3 | | 14-5p=-3p-2 | | -5x+6=-4x+-7 | | 55x=110 | | asd=5 | | 2m^2+13m=24 | | 6x^2-10x-10=0 | | 26x-11-14x=3(4x-5)+4 | | 4x-29=-1x+-4 | | 14+5x=40 | | 6x-54=4x-20 | | -17x^2+13x+13=0 | | b^2+10b= | | 0=-17x^2+13x+13 | | -7=4+x/5 | | 92x+5=32x+17 | | 2x+2=4x-18 | | 23x=240 | | 11x+6y=18 | | 7+16x=80 | | 109-7x=20x+19 | | 2(-3x+3)-6x=-6 | | y/5+4=40.5 | | 23x=80 | | 9z-11=-65+3z | | (2y-5)(3y+7)= | | 0=-16t+vt+c | | 9z-11=65+3z |